Novel statistics predict the COVID‐19 pandemic could terminate in 2022 - Chen, Ji‐Ming (Journal of medical virology, 2022)
Many people want to know when the COVID‐19 pandemic will end and life will return to normal. This question is highly elusive and distinct predictions have been proposed. In this study, the global mortality and case fatality rate of COVID‐19 were analyzed using nonlinear regression. The analysis showed that the COVID‐19 pandemic could terminate in 2022, but COVID‐19 could be one or two times more deadly than seasonal influenza by 2023. The prediction considered the possibility of the emergence of new variants of SARS‐CoV‐2 and was supported by the features of the Omicron variant and other facts. As the herd immunity against COVID‐19 established through natural infections and mass vaccination is distinct among countries, COVID‐19 could be more or less deadly in some countries in the coming years than the prediction. Although the future of COVID‐19 will have multiple possibilities, this statistics‐based prediction could aid to make proper decisions and establish an example on the prediction of infectious diseases. Highlights The global mortality and case fatality rate of COVID‐19 were statistically analyzed. The analysis provided novel statistics for the prediction of the COVID‐19 pandemic. The COVID‐19 pandemic could terminate in 2022. COVID‐19 could be one or two times more deadly than seasonal influenza by 2023.